2015
DOI: 10.1111/rda.12628
|View full text |Cite
|
Sign up to set email alerts
|

Epigallocatechin‐3‐Gallate (EGCG) Reduces Rotenone Effect on Stallion Sperm–Zona Pellucida Heterologous Binding

Abstract: Stallion spermatozoa are highly dependent on oxidative phosphorylation for ATP production to achieve normal sperm function and to fuel the motility. The aim of this study was to evaluate the response of equine sperm under capacitating conditions to the inhibition of mitochondrial complex I by rotenone and to test whether epigallocatechin-3-gallate (EGCG), a natural polyphenol component of green tea, could counteract this effect. After 2-h incubation of stallion spermatozoa in modified Tyrode's medium, rotenone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…The use of EGCG at different concentrations (10, 20, and 60 μM) significantly improved the number of semen bound to the zona pellucida (ZP) up to control levels, suggesting that GrTPs are able to decrease the damage caused by rotenone [ 102 ]. The addition of 25, 50, and 100 μM EGCG to thawed sperm for one hour did not have any effect on sperm viability and acrosome integrity but increased the in vitro penetration rate and the efficiency of fertilization [ 103 ]. GrTPs are expected to have impacts on the treatment and management of idiopathic infertility.…”
Section: Green Tea Polyphenols Improve Fertilitymentioning
confidence: 99%
“…The use of EGCG at different concentrations (10, 20, and 60 μM) significantly improved the number of semen bound to the zona pellucida (ZP) up to control levels, suggesting that GrTPs are able to decrease the damage caused by rotenone [ 102 ]. The addition of 25, 50, and 100 μM EGCG to thawed sperm for one hour did not have any effect on sperm viability and acrosome integrity but increased the in vitro penetration rate and the efficiency of fertilization [ 103 ]. GrTPs are expected to have impacts on the treatment and management of idiopathic infertility.…”
Section: Green Tea Polyphenols Improve Fertilitymentioning
confidence: 99%
“…Rotenone also induces Parkinson's disease‐like symptoms in humans and animal models . Moreover, the reproductive system, oocyte maturation, ovulation, and fertilization are affected by exposure to rotenone. However, little is known about the toxic effects of rotenone on porcine early embryo development.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study (Plaza Davila et al., ), we demonstrated that EGCG helps in protecting stallion sperm function from the negative effect induced by rotenone during in vitro induced capacitation. In that study, we did not find any difference in sperm quality parameters (acrosome reaction and viability) between treatments, but we did observe an important difference in heterologous binding capacity which was decreased by rotenone but fully restored by EGCG.…”
Section: Discussionmentioning
confidence: 56%
“…Different antioxidants have been tested on chilled stallion spermatozoa to minimize the adverse effects of oxidative stress and to improve sperm quality, but the results obtained are sometimes limited or unsatisfactory. In the present study, we tested different doses of EGCG and green tea extract polyphenols (plant molecules recognized to exert beneficial effects on spermatozoa; Plaza Davila et al., ; Wittayarat et al., , ) on stallion sperm stored at 4°C for 48 hr.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation